Translating legislative documents at the European Parliament: e-Parliament, XML, SPA and the Cat4Trad workflow - Chartier-Brun, Pascale (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2018)
The translation services at the European Parliament, under the Directorate-General for Translation, use a chain of applications – e-Parliament – and XML technologies for the automation of the translation of legislative texts and efficient reuse of translated segments. This paper presents a detailed look at the translation workflow implemented at the European Parliament with focus on Safe Protocol Automation (SPA) and the Cat4Trad translation environment.
Keywords: European Parliament; translation workflow; multilingual EU; XML; Cat4Trad; legislative documents; e-Parliament; machine translation; legal translation; translation memories, concordance; Euramis